Regulatory role of PPAR in colorectal cancer - Cong Wang; Tingcong Lv; Binghui Jin; Yang Li; Zhe Fan (Cell Death Discovery)
Abstract Colorectal cancer (CRC) is one of the most common tumors in the digestive system, and the majority of patients are found to be in advanced stages, which is a burden to human health all over the world. Moreover, in recent years, CRC has been progressively becoming younger, with an increasing incidence mainly among patients <50 years old. Despite the increase in awareness of CRC and the continuous improvement of medical treatment nowadays, the challenge of CRC still needs to be conquered. By now, the pathogenesis of CRC is complex and not fully understood. With the deepening of research, it has been revealed that PPARs, as a transcription factor, are inextricably linked to CRC. This article outlines the mechanisms by which PPARs are involved in CRC development. An in-depth understanding of the pathways related to PPARs may provide new ways of developing effective therapies for CRC with PPARs as potential targets.